ROLE OF THE REGIONAL UNIVERSITY IN THE RENAISSANCE FOLK PHYSICAL CULTURE - K. Ortabaev; U. Salpagarov (Вестник Северо-Кавказского федерального университета)
The article is devoted to the role of the regional university in the revival of folk culture and traditions of physical education. The article describes the most significant, according to the authors, forms and methods of participation of the university in the development and popularization of folk physical culture -national sports, sports games and physical exercises in the context of the further development of ethnosport, promoting a healthy lifestyle of the region's population. The role of the Karachay-Cherkess State University in improving ethnosport, physical culture and health, sports mass work in the republic on the basis of the principles of cultural conformity of regional education, the synthesis of traditions and innovations in the revival offolk traditions and physical culture of the region is characterized.